Authigenic and allogenic organic remains as an indicator of geomorphological process activity within the floodplain environment: two case studies from Racibórz Basin, southern Poland - Wójcicki, Krzysztof (Bulletin of Geography. Physical Geography Series, 2015)
Distinction between organic components accumulated in situ and those deposited by sedimentation is essential for the assessment of the intensity and extent of impact of geomorphological processes. Authigenic components include moss remains, fragments of the root systems of herbaceous plants and trees, the epidermis of rhizomes, and leaf sheaths, as well as a fungal mycelium. Among the allogenic components are aboveground parts of plants, including leaves of vascular plants, wood, epidermis and periderm, sporomorphs, sporangia, fruits and seeds, as well as zooclasts and protist remains. Microscopic grid analysis allows the share of individual morphological forms of organic matter to be determined in order to reconstruct the deposition conditions on the floodplain. This method makes it possible to detect episodes of activity of fluvial, aeolian and slope processes even when not accompanied by sedimentation of mineralogenic components.